Putting people at the center of ecosystem restoration - Mansourian, Stephanie; Elias, Marlene (2024)
This brief demonstrates the necessity of adopting people-centered and rights-based approaches to ecosystem restoration to support progress towards achieving Target 2 of the Convention on Biological Diversity’s (CBD) Kunming- Montreal Global Biodiversity Framework (KM-GBF) - Restore 30% of Degraded Ecosystems– as well as Targets 1, 3, among others, and provides recommendations for achieving this.